Real-time auditory feedback system for bow-tilt correction while aiming in archery - Ogasawara, T.; Fukamachi, H.; Aoyagi, K.; Kumano, S.; Togo, H.; Oka, K. (IEEE Xplore, 2022)
In archery, archers aim statically at a target then release an arrow; thus, bow stability during aiming is important for high performance. The stability of the bow is controlled as a part of posture by using the skeletal muscles of the trunk. Previous studies have proposed methods for measuring postural stability, but the extent to which these methods are effective in training is largely unexplored. Therefore, we introduce a real-time auditory feedback system to correct the bow stability of archers during their daily training. Our system provides audible feedback to archers when their bow is tilted from the desired vertical or upright position while aiming. The bow's tilt is measured with a small, lightweight accelerometer attached to the bow, and the system emits tones depending on the tilt angle to alert the archer to correct the bow's tilt. We conducted an experiment to verify the proposed system, and the results indicate a statistically significant 38% reduction in tilt from nine experienced university archers. This effect persisted even after the auditory feedback was turned off. Our system also helped 67% of the participants notice the deviation of their perceived tilt of the bow from the measured tilt. This experiment demonstrated the persistent effect of bow-tilt correction and the usefulness of the proposed auditory feedback system.